DAMPAK AKSESIBILITAS TRANSPORTASI DARAT DALAM PENGEMBANGAN EKONOMI WILAYAH PESISIR BERBASIS SEKTOR PERIKANAN (STUDI KASUS: PULAU AMBON, PROVINSI MALUKU) - Papilaya, Renoldy Lamberthy; Latuconsina, Jainur; Nurhaeny, Andiah (Universitas Pattimura, 2024)
The development of a city cannot be separated from the surrounding area, so that in the urban system, a city will have an interdependent impact with the immediate area around it (Putra, et al, 2022). One form of inter-regional linkage occurs in the Ambon Island area, which was formed from the combination of Ambon City and a small part of Central Maluku Regency. This center-periphery phenomenon can occur in the form of linkages between sectors that are connected using accessibility. This research aims to explain the impact of land transportation accessibility in the economic development of fisheries-based coastal areas. The data analysis method in this research includes a quantitative approach using the gravity accessibility method and multiple linear regression. This quantitative descriptive method is used to determine the influence of land transportation on the economic development of coastal areas. In this context, transportation acts as the lifeblood of the economy, because thanks to transportation, people and goods can be moved. If mobility, which is largely facilitated by the transportation system, becomes more frequent and frequent, then this shows that there is regional economic activity and development which can ultimately improve community welfare.